2004
DOI: 10.1111/j.0041-1132.2004.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of nonprogression 20 years after transfusion‐transmitted human immunodeficiency virus type‐1 infection

Abstract: Each year approximately 3 million units of fresh frozen plasma (FFP) are transfused in the US. FFP transfusions risk several complications including volume overload, allergic reactions, acute lung injury, and transmission of infectious pathogens. Most consensus guidelines list only a few clear indications for transfusion of FFP including treatment of bleeding due to multiple factor deficiencies, emergency reversal of vitamin K antagonists, and treatment of thrombotic thrombocytopenic purpura (TTP). 1 These lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition to HIV infection, survival may be influenced by the underlying medical cause for transfusion. Yet despite these disadvantages, we previously observed a high frequency of non-progression in this TAHIV cohort after 20 years of infection [ 7 ].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to HIV infection, survival may be influenced by the underlying medical cause for transfusion. Yet despite these disadvantages, we previously observed a high frequency of non-progression in this TAHIV cohort after 20 years of infection [ 7 ].…”
Section: Introductionmentioning
confidence: 98%
“…Although HLA type did not explain non-progression in this group [ 14 ], we have observed differences in CD8 T cell responses that are associated with HLA-dependent epitope recognition [ 15 ], and we have detected increased preservation of helper T cell responses in non-progressors from this cohort [ 16 , 17 ]. In addition to the well described host genetic factors which may prolong non-progression [ 7 ], recent studies have suggested an influence from innate immune mechanisms, including polymorphisms that decrease TLR function thereby reducing immune activation upon exposure to infections diseases [ 18 ], or the FcγRIIA polymorphism (R/R) which is strongly associated with progressive HIV disease as a result of impaired elimination of HIV immune complexes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%